China, Japan and the Quest for Leadership in East Asia - Dirk Nabers (German Institute of Global and Area Studies (GIGA), 2008)
The leadership of powerful states in processes of regional institutionalization is a significant, though still widely ignored topic in the field of International Relations (IR). This study asks about the theoretical conditions of effective leadership in international institution- building, using China's and Japan's roles in East Asian regionalism as an empirical test case. It addresses the question of what actually happens when states perform the role of leader. Specifically, it focuses on the process of negotiating leadership claims, and different hypotheses are presented as to the requirements of effective leadership in international affairs. The findings point to the fact that leadership is effective and sustainable when foreign elites acknowledge the leader's vision of international order and internalize it as their own. Leadership roles are often disputed and are constituted of shared ideas about self, other, and the world, relying on the intersubjective internalization of ideas, norms, and identities. – – Die Untersuchung der Führungsrolle 'mächtiger' Staaten innerhalb internationaler Institutionen im Prozess der regionalen Institutionenbildung ist ein wichtiges, aber bisher vernachlässigtes Thema der Internationalen Beziehungen (IB). Ausgehend von einer Analyse der Rollen Japans und Chinas im ostasiatischen Regionalismus fragt die Studie nach den theoretischen Bedingungen effizienter Führung. Im Mittelpunkt steht der Prozess des Aushandelns von Führungsansprüchen. Dazu werden verschiedene Hypothesen formuliert und untersucht. Wichtigstes Ergebnis der Untersuchung ist der Befund, dass Führungsrollen insbesondere dann effizient ausgestaltet werden können, wenn die politischen Eliten potenzieller Kooperationspartner die Ordnungsvorstellungen von Führungsmächten akzeptieren und in eigene politische Maßnahmen integrieren. Führungsrollen sind oft umstritten und werden durch intersubjektive Ideen, Normen und Identitäten, d.h. bestimmte Vorstellungen über das 'Selbst' und das 'Andere', konstituiert.
Keywords: F15; 300; Leadership; China; Japan; ASEAN+3; East Asian Summit (EAS)